2014
DOI: 10.2147/ijn.s57924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface-modifying ligands on the colloidal stability of ZnO nanoparticle dispersions in in vitro cytotoxicity test media

Abstract: The extrinsic physicochemical properties of nanoparticles (NPs), such as hydrodynamic size, surface charge, surface functional group, and colloidal stabilities, in toxicity testing media are known to have a significant influence on in vitro toxicity assessments. Therefore, interpretation of nanotoxicity test results should be based on reliable characterization of the NPs’ extrinsic properties in actual toxicity testing media. Here, we present a set of physicochemical characterization results for commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To obtain negatively charged ZnO NPs and bulk particles (BPs), sodium citrate was used to modify the surface. The particle coating method followed a previous study with minor modifications . Briefly, 4.0 g of ZnO NP or BP powder was added to 25 mL of 10.0 g L –1 sodium citrate solution (pH 7.0), and the solution was sonicated and stirred for 4 h in a water bath (25 °C, 40 kHz, 50 W).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain negatively charged ZnO NPs and bulk particles (BPs), sodium citrate was used to modify the surface. The particle coating method followed a previous study with minor modifications . Briefly, 4.0 g of ZnO NP or BP powder was added to 25 mL of 10.0 g L –1 sodium citrate solution (pH 7.0), and the solution was sonicated and stirred for 4 h in a water bath (25 °C, 40 kHz, 50 W).…”
Section: Methodsmentioning
confidence: 99%
“…The particle coating method followed a previous study with minor modifications. 31 Briefly, 4.0 g of ZnO NP or BP powder was added to 25 mL of 10.0 g L −1 sodium citrate solution (pH 7.0), and the solution was sonicated and stirred for 4 h in a water bath (25 °C, 40 kHz, 50 W). The coated particles were then collected by centrifugation (5000g, 40 min) and washed with deionized water three times.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…have shown decreased agglomeration of NPs in media with proteins (Schulze et al, 2008;Sager et al, 2007;Tantra et al, 2010;Kwon et al, 2014), increased agglomeration from serum proteins has been observed in other studies (Murdock et al, 2008;Caracciolo et al, 2014). In the serum-containing media, the lower zeta potential reduced electrostatic stabilization while stabilization by steric repulsion depends on the protein corona which in turn depends on the protein loading on the surface, composition of the proteins in the serum, and the surface chemistry of the particles, which in this case was not sufficient to stabilize the NH 2 -PS NP.…”
Section: Tab 3: System Specifications For the Mts Assay As Defined Bmentioning
confidence: 99%
“…The stability of nanoparticles can be a common concern due to issues such as: (a) Agglomeration occurs when nanoparticles aggregate, leading to the loss of their unique properties and reduced stability [142]. Surface modification and the use of stabilizing agents can help to prevent agglomeration by creating repulsive forces between particles [143][144][145].…”
Section: Perspectivementioning
confidence: 99%